Transcriptomic gene signatures associated with persistent airflow limitation in patients with severe asthma. Issue 3 (28th September 2017) - Hekking, Pieter-Paul; Loza, Matthew J.; Pavlidis, Stelios; De Meulder, Bertrand; Lefaudeux, Diane; Baribaud, Frederic; Auffray, Charles; Wagener, Ariane H.; Brinkman, Paul; Lutter, René; Bansal, Aruna T.; Sousa, Ana R.; et al.
A proportion of severe asthma patients suffers from persistent airflow limitation (PAL), often associated with more symptoms and exacerbations. Little is known about the underlying mechanisms. Here, our aim was to discover unexplored potential mechanisms using Gene Set Variation Analysis (GSVA), a sensitive technique that can detect underlying pathways in heterogeneous samples. Severe asthma patients from the U-BIOPRED cohort with PAL (post-bronchodilator forced expiratory volume in 1 s/forced vital capacity ratio below the lower limit of normal) were compared with those without PAL. Gene expression was assessed on the total RNA of sputum cells, nasal brushings, and endobronchial brushings and biopsies. GSVA was applied to identify differentially enriched predefined gene signatures based on all available gene expression publications and data on airways disease. Differentially enriched gene signatures were identified in nasal brushings (n=1), sputum (n=9), bronchial brushings (n=1) and bronchial biopsies (n=4) that were associated with response to inhaled steroids, eosinophils, interleukin-13, interferon-α, specific CD4 + T-cells and airway remodelling. PAL in severe asthma has distinguishable underlying gene networks that are associated with treatment, inflammatory pathways and airway remodelling. These findings point towards targets for the therapy of PAL in severe asthma. Persistent airflow limitation in severe asthma is associated with a mechanism involving IL-13 and remodelling http://ow.ly/JYcC30daSRf